Pengaruh LKS Laboratorium Virtual dalam Pendekatan Saintifik Materi Fluida Terhadap Hasil Belajar Siswa Kelas XI SMAN 14 Padang - Muhammad Tri Bimo; Asrizal Asrizal; Hidayati Hidayati (Universitas Negeri Padang, 2018)
Experiment is important to support good learning outcomes of students. However, the application of the experiment can’t be done well in school. This problem can be solved by solution is to apply the virtual laboratory student worksheet in scientific approach. Application of laboratory virtual student worksheet in scientific approach is expected to support students to learn actively so that it can improve the learning outcomes of students. This study has an aim to investigate the influence of virtual laboratory student worksheet with in scientific approach toward study outcomes of students. Quasi eksperiment is a type of study used in this research with randomized control group only design. This study has a population is all of students SMA N 14 Padang class XI the total number of 163 students. Sample takens by using purposive sampling technique. This study has several instruments consist of written test for knowledge aspect, observation sheet for attitude aspect and performance assessment sheet for skills aspect. Research data were analyzed by descriptive statistic, normality test and homogeneity test and mean comparison test. Can be stated from the data analisis the results of this investigation is the applied virtual laboratory student worksheet in scientific approach has given significant effect on physics learning outcomes of students on knowledge aspect, attitude aspect and skills aspect in class XI in SMA N 14 Padang at the siginificant level of 0.05.